Respuesta :

On the second step, the student said x - x is 2x, when it should equal 0
The second step should read
6x - 5 = 7
The student should then add 5 to each side
6x = 12
The student should then divide by 6 on both sides
x = 2

Answer:

the second and first steps. in the second part, x, should be substracted by x

so no xz should remain in the second part of the equation.

the second step would be:

6x - 5 = 7        

Hope this helped! Have a nice rest of ur day! Plz mark as brainliest!!! :D

-Lil G